2013
DOI: 10.1111/1754-9485.12035
|View full text |Cite
|
Sign up to set email alerts
|

CT enterography in obscure gastrointestinal bleeding: A systematic review and meta‐analysis

Abstract: The objective of this article is to provide a comprehensive and update overview of clinical application of CT enterography (CTE) in the evaluation of obscure gastrointestinal bleeding (OGIB). We performed a systematic review of relevant literatures in PubMed, EMBASE and The Cochrane Library and pooled the yield of CTE and the incremental yield (IY) of CTE over an alternate modality. A total of 18 studies (n = 660) reported the yield of CTE in evaluating OGIB and the pooled yield was 40% (95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 42 publications
3
50
0
2
Order By: Relevance
“…Limitations include radiation exposure for multi-phasic examinations [51], the need for IV contrast, and learning curve to allow detection of subtle vascular abnormalities. In a meta-analysis of 18 studies, CTE had a pooled yield of 40% compared to 53% for capsule endoscopy [48]. Other studies have shown similar yields for CTE [22,[55][56][57].…”
Section: Diagnostic Techniquesmentioning
confidence: 95%
See 2 more Smart Citations
“…Limitations include radiation exposure for multi-phasic examinations [51], the need for IV contrast, and learning curve to allow detection of subtle vascular abnormalities. In a meta-analysis of 18 studies, CTE had a pooled yield of 40% compared to 53% for capsule endoscopy [48]. Other studies have shown similar yields for CTE [22,[55][56][57].…”
Section: Diagnostic Techniquesmentioning
confidence: 95%
“…Capsule endoscopy has been shown to have excellent detection rates of vascular and inflammatory lesions, with superior yields compared to barium and cross-sectional imaging techniques [45,48,49]. Limitations include the risk of capsule retention [50], up to 30% rate of false-positive exams [46], up to 20-25% rate of incomplete small bowel examination [46,48], and difficulty in detecting small bowel masses, especially mural-based lesions [50][51][52][53]. In a study by Huprich et al, CT enterography (CTE) detected 9 of 9 small bowel tumors compared to 3 of 9 for capsule endoscopy [51].…”
Section: Diagnostic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…small bowel follow through. Although most radiological methods provide-just like CE-views of the entire small bowel, they are 'betrayed' by their low spatial resolution in cases of small, superficial lesions such as vascular malformations, erosions or ulcers [46,47].…”
Section: Obscure Gastrointestinal Bleedingmentioning
confidence: 99%
“…In order to achieve a high level of efficacy, optimal technique is critical, especially in evaluating patients with obscure gastrointestinal bleeding [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Further, because CT is now the greatest, single source of nonbackground ionizing radiation in the United States [23] (exposure from medical sources of ionizing radiation in 2006 accounted for 48% of the total exposure as opposed to 50% from background; CT contributes 49% of the medical exposure), dose reduction techniques should be utilized, especially in Crohn's patients, given the chronicity of their disease and the likelihood that they will have repeated examinations in their lifetime.…”
mentioning
confidence: 99%